PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD PADA MATERI PERUBAHAN SIFAT BENDA - Amalia, Melly; Panjaitan, Regina Lichteria; Aeni, Ani Nur (Jurnal Pena Ilmiah, 2017)
Background of this research is because score the students is not satisfying. In the proces of learning, the teacher is not involve the students on active proces of learning. Based on this condition, Learning Cycle model of learning is applied to be resolve this problem. This is because in Learning Cycle model of learning is centered in the student and make learning to be means. Form this reseach is classroom action research which is done in 3 cycles. Obtaine data in plan a cycle I reach 83,3%, cycle II 93,3%, cycle III 100% so reach the target. In the implementation cycle I reach 85%, cycle II 95%, and cycle III 100% so reach the target. Student activity in cycle I 41%, cycle II 77%, cycle III 100%. The result student completeness of preliminary data from 22 students just 31%, cycle I 40,9%, cycle II 72%, cycle III 91%. Therefor can concluded that implementation model of Learning Cycle can improve students learning outcome.